Long COVID: Accommodating a slippery fish. Issue 5 (7th November 2021) - Lyerly, Eric
Abstract : Post‐COVID conditions, long COVID, long‐haul COVID, post‐acute COVID, chronic COVID — these names each refer to the long‐term effects of a COVID‐19 infection. The Centers for Disease Control describes long COVID as a "wide range of new, returning, or ongoing health problems" related to COVID‐19.